Entrance of Mandapa (pillared hall) of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The passage from the mukhamandapa (front porch) leads to the mandapa (pillared hall), marked by two detached busts of Sadashiva at both sides of the entrance. Each bust portrays Sadashiva with three faces.